Religious references to art of miniatures In the Iranian school (Behzad is a model): عبدالرزاق جبار رحيل (Al-Academy, 2020)
The study examines the religious references of the art of miniatures in the Iranian school "Bahzad model" completed in Iran during the twelfth century AH, according to the controls and characteristics of the authoritative references. The researcher presented the problem of research, its importance, the need for it and its purpose, defined the terms in the research. The theoretical framework came with three investigations. The first topic of the concept of the reference in the field of knowledge, which concluded the most important features of the reference, is that each symbolic existence corresponds to a real existence and symbolic presence is an input to the realization of the reference. The reference then becomes a sign that acts as a holding entity for the semantics, and the receiver draws through the reference about the cognitive background associated with the text. The second topic, the Islamic art, its characteristics and its components, is a title for it, and what distinguishes Islamic art with characteristics unique to it is religious art. The third topic reviewed the most important Iranian schools in the art of photography. The results of the research came to analyze the selected models of the works of the miniatures artist (Behzad). The results of the research were achieved for its purpose, the most important of which is the arrangement of the photographic composition and the portrayal of human forms of different sizes according to social and religious status.